Res bibliographica: [Rezension von: Davies, Graham I., 1944-, Exodus 1-18] - Albertz, Rainer (Biblica, 2022)
Review article of Graham I. Davies, Exodus 1-18. A Critical and Exegetical Commentary. Volume 1: Chapters 1-10. Volume 2: Chapters 11-18 (International Critical Commentary). London, 2020.